Effects of auriculotherapy on weight and body mass index reduction in patients with overweight or obesity: Systematic review and meta-analysis. (February 2020) - Mendonça, Carolina Rodrigues; Coelho dos Santos, Larissa Silva; Noll, Matias; Silveira, Erika Aparecida; Arruda, Jalsi Tacon
Abstract: Objective: Auriculotherapy is based on the stimulation of reflex points in the ear. However, little is known about its weight-reducing effects. The aim of the present systematic review and meta-analysis was to investigate the effects of auriculotherapy on weight and/or (BMI) reduction in overweight or patients with obesity. Methods: Twelve articles were selected for systematic review. Four randomized controlled trials (RCTs) investigating weight reduction and five investigating BMI reduction were selected for the meta-analyzes. Results: The results revealed an association between auriculotherapy and weight reduction (WMD, 1.507; 95% CI, 0.606–2.407; p < 0.000). Auriculotherapy was also significantly associated with BMI reduction (WMD, 0.865; 95% CI, 0.533–1.196; p < 0.004). Conclusions: We found that auriculotherapy was effective in reducing weight and/or BMI in overweight or patients with obesity. However, the findings should be interpreted with caution due to heterogeneity. Highlights: Auriculotherapy was effective in reducing weight and/or BMI in overweight or patients with obesity.